2015
DOI: 10.7771/1541-5015.1499
|View full text |Cite
|
Sign up to set email alerts
|

The Purpose and Value for Students of PBL Groups for Learning

Abstract: Groups are central to problem-based learning (PBL) and educational and professional outcomes relevant to clinical education. However, PBL groups in practice may differ from theoretical conceptions of groups. Therefore, this study explored students' understandings of the purpose and value of PBL groups for their learning. We conducted a naturalistic study with novice (first-year) students at two dental schools (Australia, Ireland), using observation and interviews analyzed thematically. Students constructed PBL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 52 publications
0
22
0
5
Order By: Relevance
“…For example, according to Skinner, Braunack-Mayer, and Winning's (2015) study, Australian medical students perceived that group discussions during PBL involving uncertainty caused confusion, and they tended to prefer learning from texts rather than learning from group and PBL processes. Also, the Korean students' tendency to jump to a diagnosis of the patient's case in this study was similarly found in medical students in Western countries (e.g., de .…”
Section: Resultsmentioning
confidence: 99%
“…For example, according to Skinner, Braunack-Mayer, and Winning's (2015) study, Australian medical students perceived that group discussions during PBL involving uncertainty caused confusion, and they tended to prefer learning from texts rather than learning from group and PBL processes. Also, the Korean students' tendency to jump to a diagnosis of the patient's case in this study was similarly found in medical students in Western countries (e.g., de .…”
Section: Resultsmentioning
confidence: 99%
“…The curriculum context and the Maastricht implementation of PBL at each school have been described in detail elsewhere (Skinner, Braunack-Mayer, & Winning, 2015). In Australia, each PBL group was composed of seven students, and it was expected that each week one student would be the scribe for the session and record key information on the whiteboard, with everyone taking turns at this role.…”
Section: Methodsmentioning
confidence: 99%
“…These articles represent a wide spectrum of health professions, including medicine, nursing, dentistry, optometry, pharmacy, physical therapy, speech and hearing, and surgery, and are contributed by educators and researchers from Australia, Hong Kong, Ireland, and the United States. In addition, one article was the result of cross-country collaboration (see Skinner, Braunack-Mayer, & Winning, 2015). We are pleased to see that all these articles demonstrate an effort to move away from if to how as we look forward to a new generation of PBL research (Ravitz, 2009), that is, from investigating if PBL works to exploring ways to design effective PBL curricula and experiences, motivate and help students to learn in the PBL environment, prepare faculty for successful PBL implementation, assess diverse learning processes and outcomes, and augment PBL with learning technologies.…”
Section: Purpose and Overviewmentioning
confidence: 99%
“…In this issue, Skinner et al (2015) conducted ethnographic observations and interviews in two PBL programs in different countries to reconstruct for the reader beginning dentistry students' perceptions of and experiences with small groups throughout the PBL life cycle. A salient theme from this study is that students viewed group processes as mechanical, orderly information gathering and exchange, rather than as means to resolve uncertainties, issues, or conflicting ideas.…”
Section: Small Group Learning: Knowledge Co-construction or Informatimentioning
confidence: 99%
See 1 more Smart Citation